ANALYSIS OF GOVERNMENT PROCUREMENTS OF MEDICINES APPLIED IN RARE DISEASES THERAPY - D. V. Fedyaev (Фармакоэкономика, 2015)
the article presents the results of analysis of the state procurement of the drugs for rare diseases. The analysis was conducted on the basis of 1499 selected trade procedures on rare disease drugs procurement in 2013. The article evaluates the state of competition in procurement of monopoly and alternative drugs, the level of price reduction as a result of trading, the amount and volume of purchases in the subjects of the Russian Federation. The analysis results show that tender procedures used for the procurement of monopoly drugs are ineffective because of the lack of competition; distributors are not interested in price reduction at noncompetitive procedures. In the procurement of alternative drugs at competitive trade procedures it is possible to reach a high level of price reduction, indicating overpricing of the initial (maximum) contract price of procured drugs.